Results of use of heat flux sensors on liquid hydrogen tanks. Issue 1 (1st May 2022) - Johnson, W L; Balasubramaniam, R; Hibbs, R
Abstract: Heat flux sensors were used to characterize the performance of insulation on the Structural Heat Intercept, Insulation, and Vibration Evaluation Rig (SHIIVER), a large-scale test article designed to simulate upper stage cryogenic propellant tank thermal performance in simulated space environments. Usually, the insulation heat loads are derived from calculations removing all other heat sources and attributing the residual heat load to the insulation system. Testing for SHIIVER included the tank being just insulated with spray-on-foam insulation as well as covering the domes with multilayer insulation while leaving the barrel section insulated with spray-on-foam. Heat flux sensors were located at multiple locations on both domes as well as on the barrel section of the tank. Results from the SHIIVER testing using the heat flux sensors are compared to other calculated heat inputs for both liquid nitrogen and liquid hydrogen testing as a function of tank fill level. Further investigation into the transient nature of the SHIIVER testing including the heat flux sensors provided insight into heat flow patterns that may not have been otherwise seen using temperature sensors and calculated insulation heat loads. While the demonstrated uncertainties in the absolute values in the heat flux sensors are high, the values and the trends match well with other calculation methods. The results of SHIIVER allow for the use of heat flux sensors for measurements of insulation performance and dynamic system thermal response for future applications.